Mutational Landscape of Esophageal Squamous Cell Carcinoma in an Indian Cohort - Mangalaparthi, Kiran K.; Patel, Krishna; Khan, Aafaque A.; Manoharan, Malini; Karunakaran, Coral; Murugan, Sakthivel; Gupta, Ravi; Gupta, Rohit; Khanna-Gupta, Arati; Chaudhuri, Amitabha; Kumar, Prashant; Nair, Bipin; et al. (Frontiers in Oncology, 2020)
Esophageal squamous cell carcinoma (ESCC) is the most common histological subtype of esophageal cancer in India. Cigarette smoking and chewing tobacco are known risk factors associated with ESCC. However, genomic alterations associated with ESCC in India are not well characterized. In this study, we carried out exome sequencing to characterize the mutational landscape of ESCC tumors from subjects with a varied history of tobacco usage. The whole exome sequence analysis of ESCC from an Indian cohort revealed several genes that were mutated or had copy number changes. ESCC from tobacco chewers had a higher frequency of C:G>A:T transversions and 2-fold enrichment for mutation signature 4 compared to smokers and non-users of tobacco. Genes such as TP53, CSMD3, SYNE1, PIK3CA and NOTCH1 were found to be frequently mutated in an Indian cohort. Mutually exclusive mutation patterns were observed in PIK3CA - NOTCH1, DNAH5 – ZFHX4, MUC16 - FAT1, and ZFHX4 - NOTCH1 gene pairs. Recurrent amplifications were observed in 3q22-3q29, 11q13.3-q13.4, 7q22.1-q31.1, and 8q24 regions. Approximately 53% of tumors had genomic alterations in PIK3CA making this pathway a promising candidate for targeted therapy. In conclusion, we observe enrichment of mutation signature 4 in ESCC tumors from patients with a history of tobacco chewing. This is likely due to direct exposure of esophagus to tobacco carcinogens when it is chewed and swallowed. Genomic alterations were frequently observed in PIK3CA-AKT pathway members independent of the history of tobacco usage. PIK3CA pathway can be potentially targeted in ESCC which currently has no effective targeted therapeutic options.